DEVELOPMENT OF VISIBLE SKILLS OF STUDENTS IN HIGHER EDUCATION - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
In our article about the role of tutoring in attracting students to the university. A mentor is a person who works as a consultant or assistant. His task is to support the project with knowledge and experience. In pedagogy, a coach is a teacher, a mentor, a teacher, and a builder.